Digital Payment Adoption, Operational Efficiency, and SME Financial Performance: A Systematic Evidence Review - Thierno Abdoulaye Balde; Erna Retna Rahadjeng (Sumber Belajar Sejahtera, 2026)
This study conducts a systematic literature review to examine how digital payment adoption, particularly QR-based systems and e-wallets, relates to SME financial performance through operational efficiency. Previous studies have largely examined the direct relationship between digital payment adoption and financial performance, while the role of operational efficiency as an explanatory mechanism remains insufficiently synthesized. Guided by the SPAR-4-SLR and PRISMA frameworks, the review analyzed 29 peer-reviewed English-language articles published between 2020 and 2026 from Scopus, Web of Science, ScienceDirect, SpringerLink, and Emerald Insight. The synthesis reveals that digital payment adoption enhances operational efficiency by accelerating transaction processing, reducing administrative costs, improving financial accuracy, and strengthening transaction records. However, evidence on the direct effect of digital payment adoption on financial performance remains mixed, suggesting that adoption alone does not automatically generate financial gains. The originality of this study lies in synthesizing fragmented evidence and positioning operational efficiency as a central explanatory mechanism linking digital payment adoption to SME financial performance. The review is limited to English-language peer-reviewed articles and may not capture relevant studies in other languages or publication formats. The findings imply that SME managers, policymakers, and fintech providers should focus not only on adoption but also on operational integration, digital capability development, and the development of supportive infrastructure.